A lithium ion battery electrolyte additive composition, electrolyte, lithium ion battery

CN122968441APending Publication Date: 2026-10-23KUNSHAN SYNERGY SCIENTECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611104524.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-24
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

为了实现电解液的阻燃,目前常用向电解液中添加的磷腈类阻燃剂,但磷腈仍然存在阻燃性不足

Benefits of technology

本发明的添加剂组合物包括2,5-二氧杂己二酸二乙酯、甘露醇碳酸硫酸酯和磷腈类添加剂,其中甘露醇碳酸硫酸酯(BDD)作为硫酸酯类添加剂,可在电极表面优先发生还原反应,形成稳定的含硫界面膜,抑制电解液在电极表面的持续分解;2,5-二氧杂己二酸二乙酯(DOHDE)分子中的酯基和醚氧官能团可进一步优化界面膜的结构,提高界面膜的柔韧性和锂离子传导能力。两者协同作用,可在正负极表面形成致密、稳定、低阻抗的SEI/CEI膜,有效抑制高温循环过程中的界面副反应,显著提升电池的高温循环容量保持率。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application belongs to the technical field of lithium ion batteries, and particularly relates to a lithium ion battery electrolyte additive composition, an electrolyte and a lithium ion battery. The additive composition comprises 2,5-dioxa hexanedioic acid diethyl ester, mannitol carbonate sulfate and phosphonitrile additive. The mannitol carbonate sulfate can generate a reduction reaction on the electrode surface to form a stable sulfur-containing interface film, and the 2,5-dioxa hexanedioic acid diethyl ester can improve the flexibility and lithium ion conduction capacity of the interface film. The two can effectively inhibit the interface side reaction in the high-temperature cycle process, and significantly improve the high-temperature cycle capacity retention rate of the battery. Through the compounding of BDD and PFPN with DOHDE, the electrolyte can be more uniformly penetrated into the electrode pores, the uniformity of lithium ion distribution and the consistency of interface reaction can be improved, and the thermal stability of the battery is improved, so that the battery has a higher safety threshold under thermal abuse conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of lithium-ion battery technology, and particularly relates to a lithium-ion battery electrolyte additive composition, electrolyte, and lithium-ion battery. Background Technology

[0002] Lithium-ion batteries, with their advantages of high energy density, long cycle life, and no memory effect, have become the core technology carrier for consumer electronics, electric vehicles, and energy storage systems. However, as applications expand to complex operating conditions such as high temperature and high power, the shortcomings of batteries in terms of performance and safety are becoming increasingly prominent. In particular, cycle stability under high temperature conditions, electrolyte wettability of electrode materials, and safety under thermal abuse conditions have become key technical bottlenecks restricting their further development.

[0003] The electrolyte in a lithium-ion battery plays a crucial role in battery performance, affecting capacity, safety, and cycle life, as it serves as the medium for lithium-ion transfer. Currently, organic electrolytes are commonly used in lithium-ion batteries. The flash points of commonly used organic solvents in these electrolytes are very low, making them highly flammable. To achieve flame retardancy in the electrolyte, phosphazene-based flame retardants are often added. However, phosphazene still suffers from insufficient flame retardancy.

[0004] Therefore, there is an urgent need to develop an electrolyte additive composition that can simultaneously improve the high-temperature cycle performance, electrolyte wettability, and thermal abuse safety performance of lithium-ion batteries. Summary of the Invention

[0005] In view of the above-mentioned problems in the prior art, the present invention provides a lithium-ion battery electrolyte additive composition, electrolyte, and lithium-ion battery, which can simultaneously improve the high-temperature cycle performance, electrolyte wettability, and thermal abuse safety performance of lithium-ion batteries.

[0006] To achieve the above objectives, the technical solution provided by the present invention is as follows: In a first aspect, this application provides a lithium-ion battery electrolyte additive composition comprising: diethyl 2,5-dioxadipic acid, mannitol sulfate carbonate, and phosphazene additives.

[0007] Optionally, the phosphazene additive is at least one of trifluoroethoxypentafluorocyclotriphosphazene, pentafluoro(phenoxy)cyclotriphosphazene, ethoxypentafluorocyclotriphosphazene, hexafluorocyclotriphosphazene, tris(2,2-difluoroethyl) phosphate, bis(2,2,2-trifluoroethyl) (methylphosphonate), and diethyl (thiophen-2-ylmethyl)phosphonate.

[0008] Optionally, the mass ratio of diethyl 2,5-dioxadipic acid, mannitol sulfate carbonate, and phosphazene additives is (0.5%~3%):(0.5%~5%):(0.5%~2.5%).

[0009] Optionally, the phosphazene additive is ethoxypentafluorocyclotriphosphazene.

[0010] Optionally, the invention also includes auxiliary additives, said auxiliary additives being at least one selected from adiponitrile, butadionitrile, 1,3,6-hexanetrionitrile, trans-hexenedionitrile, trans-butenedionitrile, 1,2-di(cyanoethoxy)ethane, and 1,2,3-tri(cyanoethoxy)propane.

[0011] Secondly, this application also provides a lithium-ion battery electrolyte comprising a non-aqueous organic solvent, a lithium salt, and a lithium-ion battery electrolyte additive composition as described in the first aspect.

[0012] Optionally, by mass content, the non-aqueous organic solvent in the electrolyte accounts for 50% to 80%.

[0013] Optionally, by mass content, the electrolyte contains 0.5-3% diethyl 2,5-dioxadipic acid, 0.5-5% mannitol sulfate carbonate, and 0.5-2.5% phosphazene additives.

[0014] Optionally, the mass percentage of auxiliary additives in the electrolyte is 2-4% by mass content.

[0015] Optionally, the lithium salt is one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorooxalate borate, lithium dioxalate borate, lithium difluorophosphate, lithium difluorodioxalate phosphate, and lithium tetrafluorooxalate phosphate.

[0016] Optionally, the non-aqueous organic solvent is one or more of the following: ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, methyl propyl carbonate, methyl butyl carbonate, methyl formate, ethyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, butyl acrylate, methyl butyrate, ethyl butyrate, propyl butyrate, and butyl butyrate.

[0017] Thirdly, this application also provides a lithium-ion battery comprising a positive electrode, a negative electrode, and the lithium-ion battery electrolyte described in the second aspect.

[0018] Optionally, the negative electrode comprises silicon carbon and graphite; the non-aqueous organic solvent comprises a carboxylic acid ester solvent; the carboxylic acid ester solvent includes ethyl propionate; and each component meets the following requirements: 0 ≤ a / B + 10b / A < B / A; Where A represents the mass percentage of silicon carbon in the total amount of silicon carbon and graphite; B represents the mass percentage of ethyl propionate in a carboxylic ester solvent; a represents the mass percentage of diethyl 2,5-dioxadipic acid in the electrolyte; b represents the mass percentage of mannitol sulfate carbonate in the electrolyte; c represents the mass percentage of phosphazene additives in the electrolyte.

[0019] Compared with the prior art, the present invention has at least the following beneficial effects: The additive composition of this invention comprises diethyl 2,5-dioxadipic acid, mannitol sulfate carbonate, and phosphazene additives. Mannitol sulfate carbonate (BDD), as a sulfate ester additive, preferentially undergoes a reduction reaction on the electrode surface to form a stable sulfur-containing interfacial film, inhibiting the continuous decomposition of the electrolyte on the electrode surface. The ester group and ether oxygen functional groups in the diethyl 2,5-dioxadipic acid (DOHDE) molecule further optimize the structure of the interfacial film, improving its flexibility and lithium-ion conductivity. The synergistic effect of both components forms a dense, stable, and low-resistance SEI / CEI film on the positive and negative electrode surfaces, effectively suppressing interfacial side reactions during high-temperature cycling and significantly improving the high-temperature cycle capacity retention rate of the battery.

[0020] In this invention, DOHDE molecules possess strong polarity and good wetting properties, which can enhance the wettability of the electrolyte to the electrode material. When BDD and PFPN are combined with DOHDE, the contact angle between the electrolyte and the electrode material can be further reduced, allowing the electrolyte to penetrate more uniformly into the electrode pores, thus improving the uniformity of lithium ion distribution and the consistency of interfacial reactions.

[0021] Ethoxypentafluorocyclotriphosphazene (PFPN) is rich in phosphorus and phosphorus (P) and can play a flame-retardant role by capturing highly reactive free radicals to interrupt the combustion chain reaction. Furthermore, it can participate in the construction of an interface layer rich in inorganic substances (such as LiF) on the electrode surface, improving the thermal stability of the electrode. In this application, the presence of DOHDE and BDD optimizes the dispersibility and interfacial film-forming behavior of PFPN in the electrolyte. The synergistic effect of these three components enhances the thermal stability of the battery, giving it a higher safety threshold under thermal abuse conditions. Detailed Implementation

[0022] The present invention will now be described in further detail: Unless otherwise specified, the experimental methods used in the embodiments of this invention are all conventional methods.

[0023] All reagents and materials used in this example can be purchased routinely. The quantitative experiments involved in the examples were all repeated at least three times, and the results were averaged.

[0024] Raw material source: Conductive agent carbon black: Cabot (China) Investment Co., Ltd.; Adhesive: Polyvinylidene fluoride (PVDF): Jiangsu Yite New Materials Co., Ltd. Carbon nanotubes (CNTs): Jiangsu Tiannai Technology Co., Ltd. Silicon-carbon: Jiangxi Yijin New Energy Technology Co., Ltd.; Adhesive: Styrene-butadiene rubber (SBR): JSR Corporation, Tokyo, Japan; Polyacrylic acid: Meishan Yindile Technology Co., Ltd.; Thickener: Lithium carboxymethyl cellulose: Chongqing Shuoyingfeng New Energy Technology Co., Ltd.

[0025] Example 1 A lithium-ion battery is prepared by the following steps: Electrolyte preparation: The solvent was prepared in an argon-filled glove box (water and oxygen content both <0.01ppm). The mass ratio of each component in the solvent was as follows: ethylene carbonate : propylene carbonate : carboxylic acid ester (total of ethyl propionate and propyl propionate) = 2 : 0.5 : 7.5, wherein ethyl propionate accounted for 60% of the mass of the carboxylic acid ester. The mass percentage of each component in the electrolyte is as follows: Lithium salt (lithium hexafluorophosphate (LiPF6)): 12.5%; Fluorinated ethylene carbonate: 13%; 1,3,6-hexanetrionitrile: 2%; Additive composition: DOHDE, BDD and PFPN account for 1.0%, 1.0% and 1.0% of the electrolyte mass, respectively; The rest are solvents; The above electrolyte raw materials are mixed to obtain an electrolyte, which is then stirred evenly to obtain the electrolyte of Example 1 of the present invention.

[0026] Preparation of the positive electrode sheet: Lithium cobalt oxide (LiCoO2), carbon black (conductive agent), polyvinylidene fluoride (PVDF) (binder), and carbon nanotubes (CNTs) were mixed in a mass ratio of 98:0.5:1.1:0.4 to obtain a mixture. This mixture was then added to N-methylpyrrolidone solvent and stirred thoroughly (the amount of the mixture added was 30 wt% of the N-methylpyrrolidone solvent) to form a uniform positive electrode slurry. The positive electrode slurry was then coated onto an Al foil (10 μm thick) and dried (the double-sided density of the positive electrode was 300 g / cm³). 2Then it is rolled (compacted density 4.15 g / cm³). 3 ), thus obtaining the positive electrode sheet.

[0027] Preparation of the negative electrode sheet: The following raw materials for the negative electrode, graphite, silicon carbon (accounting for 10 wt% of the total negative electrode material (graphite and silicon carbon)), styrene-butadiene rubber (a binder), polyacrylic acid, lithium carboxymethyl cellulose (a thickener), and carbon nanotubes (CNTs) were weighed according to a mass ratio of 86.85:9.65:1.5:1.5:0.25:0.25. These were thoroughly mixed in an appropriate amount of deionized water solvent to form a uniform negative electrode slurry. The negative electrode slurry was then coated onto a copper foil (8 μm thick) and dried (the negative electrode areal density was 123.6 g / cm³). 2 Roller compaction (compacted density 1.60 g / cm³) 3 ), thus obtaining the negative electrode sheet.

[0028] The diaphragm is made of 9μm thick polyethylene (PE) membrane, of which the base membrane is 7μm thick and there is a 2μm aluminum oxide coating on both sides of the base membrane.

[0029] The positive electrode, negative electrode and separator are wound and assembled into a cell. The bare cell is placed in an outer packaging shell, dried and injected with electrolyte. Then, vacuum sealing, settling, formation, shaping and capacity testing are carried out to obtain a soft-pack lithium-ion battery.

[0030] Example 2

[0031] The difference between this embodiment and Embodiment 1 is that the amounts of DOHDE, BDD and PFPN added to the electrolyte are 1.5%, 1.0% and 1.0% of the total mass of the electrolyte, respectively.

[0032] Example 3

[0033] The difference between this embodiment and Embodiment 1 is that the amounts of DOHDE, BDD and PFPN added to the electrolyte are 1.5%, 1.5% and 1.0% of the total mass of the electrolyte, respectively.

[0034] Example 4

[0035] The difference between this embodiment and Embodiment 1 is that the amounts of DOHDE, BDD and PFPN added to the electrolyte are 2%, 1.5% and 1.0% of the total mass of the electrolyte, respectively.

[0036] Comparative Example 1 The difference between this comparative example and Example 1 is that the amount of DOHDE, BDD and PFPN added to the electrolyte is 0.

[0037] Comparative Example 2 The difference between this comparative example and Example 1 is that the amounts of DOHDE, BDD and PFPN added to the electrolyte are 0%, 0% and 1.0% of the total mass of the electrolyte, respectively.

[0038] Comparative Example 3 The difference between this comparative example and Example 1 is that the amounts of DOHDE, BDD and PFPN added to the electrolyte are 0%, 1.0% and 1.0% of the total mass of the electrolyte, respectively.

[0039] Performance testing: 1. High-temperature cycling performance test: The batteries of Examples 1-4 and Comparative Examples 1-3 were subjected to charge-discharge cycle tests at 1C / 1C current density in a 45°C constant temperature chamber, with a voltage range of 3~4.55V, and the capacity retention rate was recorded after 500 cycles.

[0040] 2. Electrolyte wettability test: A contact angle meter was used to test the contact angles of the electrolytes in Examples 1-4 and Comparative Examples 1-3 on the LCO positive electrode and the silicon-carbon negative electrode, respectively. The smaller the contact angle, the better the wettability.

[0041] 3. Thermal abuse test (hot chamber test) The batteries from Examples 1-4 and Comparative Examples 1-3 were charged at a constant current of 0.5C to 4.55V, and then charged at a constant voltage of 4.55V until the current dropped to 0.05C. They were then left to stand at 25±0.5℃ for 60 minutes. The temperature was then increased to 150℃±2℃ at a rate of 5℃ / min and held for 30 minutes. The batteries were observed for signs of fire or smoke, and the pass rate was recorded.

[0042] 4. Needle prick test The batteries of Examples 1-4 and Comparative Examples 1-3 were charged to full capacity at a constant current of 0.5C. A high-temperature resistant steel needle with a diameter of 3mm was inserted into the battery at a speed of 20mm / s, and the battery was observed to see if it caught fire or exploded.

[0043] 5. High-temperature storage performance test The batteries of Examples 1-4 and Comparative Examples 1-3 were stored at 85°C for 6 hours, and the change in battery thickness before and after storage was tested. A thickness of ≤15 mm was considered acceptable.

[0044] The performance test results are shown in Table 1.

[0045] Table 1: Performance Test Results a(%) 0 0 0 1 1.5 1.5 2 b(%) 0 0 1 1 1 1.5 1.5 c(%) 0 1 1 1 1 1 1 A(%) 10 10 10 10 10 10 10 B(%) 60 60 60 60 60 60 60 a / B+10b / A 0 0 1 1.017 1.025 1.525 1.533 B / A 6 6 6 6 6 6 6 Capacity retention rate at 45℃ / 500 cycles (%) 55 65 68 81.0 81.5 83 85.4 Electrolyte wettability test (°) 40 38 35 28 26 25 25 150℃ hot box test pass rate (%) 40 50 70 100 100 100 100 Needle prick test pass rate (%) 20 30 60 100 100 100 100 85℃-6H (Is it acceptable?) no no no yes yes yes yes As shown in Table 1, the batteries of Examples 1-4 of the present invention are significantly better than those of Comparative Examples 1-3 in terms of high-temperature cycle performance, electrolyte wettability, thermal abuse safety performance and high-temperature storage performance. This indicates that there is a significant synergistic effect among the three additives DOHDE, BDD and PFPN, and the combined use of the three can comprehensively improve the overall performance of lithium-ion batteries.

[0046] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to the specific implementations described. Clearly, many modifications and optimizations can be made based on the content of this specification. The embodiments selected and specifically described in this specification are intended to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and apply the invention. The invention is limited only by the claims and their full scope and equivalents.

Claims

1. A lithium-ion battery electrolyte additive composition, characterized in that, include: Diethyl 2,5-dioxadipic acid, mannitol sulfate and phosphazene additives.

2. The lithium-ion battery electrolyte additive composition according to claim 1, characterized in that, The mass ratio of the diethyl 2,5-dioxadipic acid, mannitol sulfate carbonate, and phosphazene additives is (0.5%~3%):(0.5%~5%):(0.5%~2.5%).

3. The lithium-ion battery electrolyte additive composition according to claim 1, characterized in that, The phosphazene additive is at least one of trifluoroethoxypentafluorocyclotriphosphazene, pentafluoro(phenoxy)cyclotriphosphazene, ethoxypentafluorocyclotriphosphazene, hexafluorocyclotriphosphazene, tris(2,2-difluoroethyl) phosphate, bis(2,2,2-trifluoroethyl)(methylphosphonate), and diethyl (thiophen-2-ylmethyl)phosphonate.

4. The lithium-ion battery electrolyte additive composition according to claim 1, characterized in that, The phosphazene additive is ethoxypentafluorocyclotriphosphazene.

5. A lithium-ion battery electrolyte, characterized in that, The composition comprises a non-aqueous organic solvent, a lithium salt, and a lithium-ion battery electrolyte additive composition according to any one of claims 1-4.

6. The lithium-ion battery electrolyte according to claim 5, characterized in that, By mass content, the electrolyte contains 0.5-3% diethyl 2,5-dioxaadipic acid, 0.5-5% mannitol carbonate sulfate, and 0.5-2.5% phosphazene additives.

7. The lithium-ion battery electrolyte according to claim 5, characterized in that, The lithium salt is one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorooxalate borate, lithium dioxalate borate, lithium difluorophosphate, lithium difluorodioxalate phosphate, and lithium tetrafluorooxalate phosphate.

8. The lithium-ion battery electrolyte according to claim 5, characterized in that, The non-aqueous organic solvent is one or more of the following: ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, methyl propyl carbonate, methyl butyl carbonate, methyl formate, ethyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, butyl acrylate, methyl butyrate, ethyl butyrate, propyl butyrate, and butyl butyrate.

9. A lithium-ion battery, characterized in that, It comprises a positive electrode, a negative electrode, and the lithium-ion battery electrolyte as described in any one of claims 5-8.

10. The lithium-ion battery according to claim 9, characterized in that, The negative electrode comprises silicon-carbon and graphite; the non-aqueous organic solvent comprises carboxylic acid ester solvents; the carboxylic acid ester solvent includes ethyl propionate; each component meets the following requirements: 0 ≤ a / B + 10b / A < B / A; Where A represents the mass percentage of silicon carbon in the total amount of silicon carbon and graphite; B represents the mass percentage of ethyl propionate in a carboxylic ester solvent; a represents the mass percentage of diethyl 2,5-dioxadipic acid in the electrolyte; b represents the mass percentage of mannitol sulfate carbonate in the electrolyte; c represents the mass percentage of phosphazene additives in the electrolyte.